Investigation of the microstructure of TC1/1060/6061 explosive composites based on experiments and numerical simulations. (1st April 2022) - Yuan, Jiaxin; Shao, Fei; Bai, Linyue; Zhang, Hongwei; Xu, Qian; Gao, Lei; Ma, Qingna
Abstract: In this study, the microstructure of TC1/1060/6061 composites manufactured by explosive welding was investigated using experiments and numerical simulations. The results showed that the two interfaces of the TC1/1060/6061 composites exhibited an overall linear bonding interface without defects such as macroscopic cracks or pores. A melting layer caused by the adiabatic compression of air was observed, and the overall welding quality of the composites was good. There were no intermetallic compounds observed at the TC1/1060 interface, and the diffusion area was short, which formed a metallurgical bond. After heat treatment, the grains on the base plate and interlayer side of the composites formed a cubic recrystallized texture, while the grains on the flyer plate side developed a fine-grained structure. The microhardness of the base plate and flyer plate was higher closer to the interface due to the process hardening effect, while the microhardness of the interlayer remained stable. The formation process of these two interfaces was analyzed by numerical simulations, and jetting was observed at the 1060/6061 interface. The TC1/1060 interface in the numerical simulations showed a linear morphology, and the 1060/6061 interface showed a microwave morphology.